Petrography, Mineralogy and Diagenetic history of the Sarmord Formation (Valanginian-Aptian) in selected areas, Northeastern Iraq - Saleh, Safaa A.; Tamar-Agha, Mazin Y.; Balaky, Sardar M. (Iraqi Journal of Science, 2023)
This research studies the petrography, mineralogy and diagenetic history of the Sarmord Formation at Sulaimani and Erbil Governorates in Northeastern Iraq. The Sarmord Formation consists mainly of alternated yellowish to bluish gray bedded marly limestone with yellowish gray soft marl beds. Petrographic investigations of the marly limestones were based on 270 thin sections and show that the skeletal grains include bioclasts, foraminiferas, radiolarians, calcispheres, echinoderms, ostracods and cephalopods. The groundmass is composed of micrite with light brown to gray colors, rich in organic materials and iron oxides. The X-ray diffraction analysis of the marls revealed that the abundant clay minerals in the Sarmord Formation are kaolinite and smectite -illite mixed layers, in addition to chlorite traces, which may indicate an increasing influx of detrital minerals from the continental weathering because of the humid Early Cretaceous climate. Non-clay minerals include calcite and quartz with subordinate feldspars. The main diagenetic processes affecting the Sarmord Formation carbonates are micritization, dissolution, cementation, compaction, dolomitization, dedolomitization and authigenic minerals (pyrite and silica). These belong to three diagenetic stages; early (shallow burial), middle and late (deep burial).